2017
DOI: 10.1088/1361-665x/aa59d7
|View full text |Cite
|
Sign up to set email alerts
|

Damage detection of structures with detrended fluctuation and detrended cross-correlation analyses

Abstract: Recently, fractal analysis has shown its potential for damage detection and assessment in fields such as biomedical and mechanical engineering. Because of its practicability in interpreting irregular, complex, and disordered phenomena, a structural health monitoring (SHM) system based on detrended fluctuation analysis (DFA) and detrended crosscorrelation analysis (DCCA) is proposed. First, damage conditions can be swiftly detected by evaluating ambient vibration signals measured from a structure through DFA. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…A laboratory experimental investigation based on an end-fixed steel beam showed that CorV can be used for structural damage detection [13]. Lin and Fajri proposed a structural health monitoring (SHM) system based on detrended fluctuation analysis (DFA) and detrended cross-correlation analysis (DCCA); the performance of the SHM system was verified using a four-layer numerical model [14]. Huo et al combined cross-correlation function amplitude (CCFA) with a support vector machine (SVM) for damage detection of a bone structure [15].…”
Section: Introductionmentioning
confidence: 99%
“…A laboratory experimental investigation based on an end-fixed steel beam showed that CorV can be used for structural damage detection [13]. Lin and Fajri proposed a structural health monitoring (SHM) system based on detrended fluctuation analysis (DFA) and detrended cross-correlation analysis (DCCA); the performance of the SHM system was verified using a four-layer numerical model [14]. Huo et al combined cross-correlation function amplitude (CCFA) with a support vector machine (SVM) for damage detection of a bone structure [15].…”
Section: Introductionmentioning
confidence: 99%
“…Nagarajaiah and Basu summarized the pros and cons of short time Fourier transform, wavelet transform, and Hilbert-Huang transform application in structural seismic damage detection [26]. e features of nonlinear system such as fractal dimension (FD) and chaos were also used as nonlinear indicator function [27][28][29][30]. Li et al proposed a datadriven approach using the time-frequency feature (TFF) for shear-type buildings where the FD of TFF at each DOF for linear system was derived with the help of modal superposition principle, and the FD of TFF for each substructure in nonlinear system was derived with the help of substructure method [31].…”
Section: Introductionmentioning
confidence: 99%